Does implementation of a tailored intervention increase adherence to a National Safety and Quality Standard? A study to improve delirium care. (15th January 2021) - Oberai, Tarandeep; Laver, Kate; Woodman, Richard; Crotty, Maria; Kerkhoffs, Gino; Jaarsma, Ruurd
Abstract: Background: Delirium is commonly detected in older people after hip fracture. Delirium is considered to be a multifactorial disorder that is often seen post-operatively (incidence ranging from 35% to 65%). Hospitals in Australia are required to meet eight standards including the comprehensive care standard to be able to maintain their accreditation. The standard includes actions related to falls, pressure injuries, nutrition, mental health, cognitive impairment and end-of-life care. Delirium prevention was identified as an area for improvement in our Orthopaedic unit in a Level 1 University Trauma Centre in Australia. This implementation research project aimed to understand the efficacy of a delirium prevention intervention within an existing orthopaedic speciality care system. Objective: Implementation of the tailored intervention will increase adherence to National Safety and Quality Health Service Standards, thereby reducing rate of delirium. Methods: In this study, we used an interrupted time series design to examine changes in practice over time in people admitted to hospital with a hip fracture. Clinical staff caring for patients with hip fracture in an acute care setting in Adelaide, South Australia, participated in the project. In brief, intervention included education, environmental restructuring, change champions, infographics and audit feedback reports. The primary outcome of interest was rate of delirium. The secondary outcome was compliance with the use of delirium 4AT screening tool, duration of delirium and hospital length of stay. Results: The rate of change per month in patients with delirium decreased significantly by 19.2%. There was no significant change observed in trend for duration of delirium and length of hospital stay between pre-intervention and post-intervention phases. A significant increase in the use of screening tool was observed from 4.7% in the pre-intervention phase to 33.6% in the post-intervention phase. Conclusion: Translation of evidence-based intervention model incorporating well-considered implementation strategies had a mixed impact on decreasing the rate of delirium. The scheduled hospital accreditation enhanced the use of validated screening tool to recognize delirium. This project highlights the importance of aligning implementation goals with the wider goals of the organization as well as making clinicians accountable by consistent auditing.